STUDY OF SURFACTANT ADSORPTION ON COLLOIDAL PARTICLES - Cummins, P; Staples, E; Penfold, J (1990)
Surface tension and small-angle neutron scattering have been used to study the nature of surfactant adsorption on silica sols. This paper presents results on the characterization of the ludox silica sol and adsorbed layers of hexaethylene glycol monododecyl ether (C12E6). Preliminary results are presented that demonstrate the presence of a lower consolute boundary for the composite system. © 1990 American Chemical Society.